One-pot synthesis of water-soluble, β-cyclodextrin-based polyrotaxanes in a homogeneous water system and its use in bio-applications. Issue 26 (8th June 2015) - Yu, Shuling; Yuan, Jintao; Shi, Jiahua; Ruan, Xiaojiao; Wang, Yali; Gao, Shufang; Du, Yu
Abstract : The water-soluble and biocompatible PR, synthesized in a homogeneous system, can largely accumulate in tumors for a long time. Abstract : A small, nano-sized, water-soluble polyrotaxane (PR) was synthesized using a highly efficient one-pot synthesis strategy in a homogeneous water system, formed from β-cyclodextrin-(COOH)2, poly(propylene glycol)bis(2-aminopropyl ether) (PPG, 2 kDa) and a mono-(6-azido-6-desoxy)-β-cyclodextrin stopper via room temperature click chemistry. β-cyclodextrin-(COOH)2 and PR were characterized by one- and two-dimensional NMR as well as by high resolution transmission electron microscopy (HR-TEM). The number of carboxyl groups in one PR was determined by 1 H NMR. Two-dimensional diffusion-ordered NMR spectroscopy (2D DOSY) and nuclear Overhauser enhancement spectroscopy (2D NOESY) show that β-cyclodextrin-(COOH)2 and PPG successfully formed an inclusion complex. HR-TEM revealed the morphology of water-soluble PR as a spherical nanoparticle with a size of approximately 3.5 nm ± 1.5 nm. PR was labeled with rhodamine to assess its biocompatibility and cell membrane penetrability in vitro . The in vivo real-time fluorescent imaging biodistribution experiments indicated that water-soluble PR can actively target tumor sites using an enhanced permeability and retention (EPR) effect, with a significantly prolonged blood circulation time in tumor-bearing mice.